A low cost, low power sap flux device for distributed and intensive monitoring of tree transpiration. (October 2022) - Beslity, Justin; Shaw, Stephen B.; Drake, John E.; Fridley, Jason; Stella, John C.; Stark, Jordan; Singh, Kanishka
Graphical abstract: Abstract: Accurate estimation of transpiration in individual trees is important for understanding plant responses to environmental drivers, closing the water balance in forest stands and catchments, and calibrating earth system models, among other applications. However, the cost and power consumption of commercial systems based on sap flow methods still limit their usage. We developed and tested a cost-effective (<$150), simple to construct, and energy efficient sap flux device based on the heat pulse method. Energy savings were achieved by reducing the voltage of heat pulses and using an internal clock to completely shut down the device between pulses. Device accuracy was confirmed by laboratory estimates of sap flow made on excised branches of Acer saccharum and Tsuga canadensis (adjusted R 2  = 0.96). In a 174-d field installation of 12 devices, batteries (eight rechargeable Ni-MH AA) needed to be replaced every 14 days. Sap flux measurements in the field tracked expected variations in vapor pressure deficit and tree phenology. The low cost, compact design, reliability, and power consumption of this device enable sap flux studies to operate with more replication and in more diverse ecological settings than has been practical in the past.